(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
: Nonalcoholic fatty liver disease (NAFLD) combines with a variety of liver pathologies, including hepatic steatosis, nonalcoholic steatohepatitis, fibrosis and cirrhosis, and acts as hepatic manifestation of metabolic syndrome. Not only the liver is a target organ in the formation of metabolic syndrome: also exist a possibility of gallbladder, pancreas and biliary tract steatosis. Fatty infiltration of the pancreatobiliary system associates with disturbance of digestive processes that promotes dysbiotic changes and intestinal disorders. Changes in intestinal microbiota, in turn, may induce systemic inflammatory response and promote NAFLD development and progression.